(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
Five states in Malaysia including Perak, Terengganu, Selangor, Melaka and Negeri Sembilan have introduced their own waqf (Islamic endowment) laws. Five other states are working on new laws and the remaining states maintain waqf matters in the general statutes on administration of Islamic law. Using the doctrinal approach and comparative analysis method, this study reviews the latest development and discusses how the changes in the laws have helped in improving slow and restricted jurisdiction in dealing with waqf. The findings show that the new Enactments have addressed most of the observations made in previous literatures, especially as regards the challenges in waqf development. Observations are also made regarding the fast development of waqf in tandem with various other aspects of the economy and the financial sector, including how waqf is now recognized as the third most significant economic sector. Moving forward, waqf must focus on synergy and innovation as well as employing new instruments with clearer vision and empowerment of institution through law. Keywords: waqf, Waqf Enactment, Islamic finance, third sector of economy